Rapid detection of clindamycin resistance in Bacteroides spp. - Murray, P R (1983)
High-level resistance to clindamycin can be accurately detected by the Wadsworth disk identification test. Of the 98 isolates of the Bacteroides fragilis group that were tested, 90 were inhibited by the 60-micrograms erythromycin disk and had clindamycin minimal inhibitory concentrations of less than or equal to 3.2 micrograms/ml. Of the remaining eight isolates, all were resistant to the erythromycin disk and had clindamycin minimal inhibitory concentrations of greater than or equal to 100 micrograms/ml.